2020
DOI: 10.1002/rmv.2170
|View full text |Cite
|
Sign up to set email alerts
|

Viral infection neutralization tests: A focus on severe acute respiratory syndrome‐coronavirus‐2 with implications for convalescent plasma therapy

Abstract: Summary Viral neutralization tests (VNTs) have long been considered old‐fashioned tricks in the armamentarium of fundamental virology, with laboratory implementation for a limited array of viruses only. Nevertheless, they represent the most reliable surrogate of potency for passive immunotherapies, such as monoclonal or polyclonal antibody therapy. The recent interest around therapy with convalescent plasma or monoclonal antibodies for the Covid‐19 pandemic has paralleled the revival of VNTs. We rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 131 publications
1
49
1
4
Order By: Relevance
“…Our results were in accordance with previous studies on other coronaviruses showing a significantly higher sensitivity of antibody tests based on the N protein (13,14). This could be attributed to the fact that the majority of antibodies are raised against the N protein, while antibodies against the S protein are considered more specific and associated with a neutralizing capacity (15,16). It is worth noting that recent studies showed a decline in the IgG antibodies against the N protein over time, while the response to the S protein was proven to be more stable (17).…”
Section: Discussionsupporting
confidence: 93%
“…Our results were in accordance with previous studies on other coronaviruses showing a significantly higher sensitivity of antibody tests based on the N protein (13,14). This could be attributed to the fact that the majority of antibodies are raised against the N protein, while antibodies against the S protein are considered more specific and associated with a neutralizing capacity (15,16). It is worth noting that recent studies showed a decline in the IgG antibodies against the N protein over time, while the response to the S protein was proven to be more stable (17).…”
Section: Discussionsupporting
confidence: 93%
“…3 However, higher hopes have been raised from the efficacy signals obtained with convalescent plasma (CP) therapy, 4 where the active substances are assumed to be polyclonal neutralizing antibodies (nAb). The interpretation of trials on CP efficacy has been largely hampered by the lack of standardized doses and poor assessment of nAb with viral neutralization tests; 5 nevertheless, favorable preliminary results have led immediately to research and development of pharmaceutical-grade hyperimmune sera 6 and mAbs ( Figure 1). These mAbs have several obvious advantages over CP and immune sera ( Table 1), given that the number of therapeutic antibodies is restricted to one or two per treatment: (a) selection of the most potent candidates (with IC 50 or the more reliable 7,8 IC100 parameter in the subnanomolar to low picomolar range); (b) better assessment of the therapeutic dose per body weight; c) exclusion of the so-called antibody-dependent enhancement (ADE) phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…In SARS, 5 mL/kg of plasma at a titer ≥1:160 was utilized ( Cheng et al, 2005 ). Such titer needs to be specified through the viral neutralization assay (VNT), thus obviating any bias from the use of diverse surrogate tests having poor correlation with the VNT ( Focosi et al, 2020a , Focosi et al, 2020b , Focosi et al, 2020c ). Additionally, given the fast-declining kinetics of nAb titers, the VNT should be assessed on each donated unit in the case of repeated donations, rather than assuming the same value across multiple donations.…”
mentioning
confidence: 99%
“…The data available suggest that late stage disease (ICU admission/ventilator support) is unlikely to respond to CCP therapy ( Agarwal et al, 2020 ), with several authors suggesting an optimal window as short as 44 h post-hospitalization for transfusing CCP ( Salazar et al, 2020a , Salazar et al, 2020b ). It is a well-known phenomenon that nAb titer correlates with the severity of symptoms in COVID-19 patients ( Focosi et al, 2020a , Focosi et al, 2020b , Focosi et al, 2020c ) and preliminary reports suggested that CCP was only effective in early stage disease ( Focosi et al, 2020a , Focosi et al, 2020b , Focosi et al, 2020c ), thus trials targeting late treatment in severe patients are unlikely to produce useful insights. Limiting RCTs to early stage disease, despite the limitations imposed on the modality, should allow a higher probability of success.…”
mentioning
confidence: 99%
See 1 more Smart Citation